Unlocking the potential of iPSC-derived immune cells: engineering iNK and iT cells for cutting-edge immunotherapy - Fang, Minggang; Allen, Alexander; Luo, Chong; Finn, Jonathan D. (Frontiers in Immunology, 2024)
Induced pluripotent stem cells (iPSCs) have emerged as a revolutionary tool in cell therapies due to their ability to differentiate into various cell types, unlimited supply, and potential as off-the-shelf cell products. New advances in iPSC-derived immune cells have generated potent iNK and iT cells which showed robust killing of cancer cells in animal models and clinical trials. With the advent of advanced genome editing technologies that enable the development of highly engineered cells, here we outline 12 strategies to engineer iPSCs to overcome limitations and challenges of current cell-based immunotherapies, including safety switches, stealth edits, avoiding graft-versus-host disease (GvHD), targeting, reduced lymphodepletion, efficient differentiation, increased in vivo persistence, stemness, metabolic fitness, homing/trafficking, and overcoming suppressive tumor microenvironment and stromal cell barrier. With the development of advanced genome editing techniques, it is now possible to insert large DNA sequences into precise genomic locations without the need for DNA double strand breaks, enabling the potential for multiplexed knock out and insertion. These technological breakthroughs have made it possible to engineer complex cell therapy products at unprecedented speed and efficiency. The combination of iPSC derived iNK, iT and advanced gene editing techniques provides new opportunities and could lead to a new era for next generation of cell immunotherapies.